The culture and titles of the kings of ancient Algeria in the balance of great powers ’’ Syphax and Massinissa as models - zinelabidine, AlTayeb (The Algerian Historical Journal, 2026)
Far from flattering the kings of ancient Algeria and free of historical emotions culture, this study was not aimed at highlighting the high literature they left in making the country a multicultural centre, both local and global, Even for scientists and intellectuals from within and outside the country to the extent that they are subjected to the so-called political and cultural titles that have in fact created a reconciliation of the Numedian cultural heritage with international sovereignty. as they have given multiple knowledge its place and established cultural milestones that have become the destination of thinkers and renowned scientific elites, As a further result, given their aspiration to the rest of the world's cultures and despite the diversity of population groups rights ", they were interested in their place among their various contemporary superpowers.